Transformational Leadership Of Headmasters In Improving Teacher Professionalism Competence In Bone Regency - Nurul Amalia Muin; Putri Nurjayana Muin; Ansar; Hasan (PT. Global Research Collaboration, 2026)
This study describes how the principals of SMKN 3 Bone and SMAN 11 Bone implement transformational leadership to improve teachers' professional competence. The research uses a qualitative, embedded multiple-case study design. Informants are selected through purposive and snowball sampling, and data are collected using triangulation. The selected resource persons were the principal of State Vocational School 3 Bone, the vice principal for academic affairs, a productive senior teacher majoring in Computer Engineering and Networks, a new teacher majoring in Office Management, the principal of SMAN 11 Bone, the vice principal for curriculum affairs, a senior teacher for Physics, and a new teacher for History. The data analysis technique used is the Qualitative Data Analysis Model of Miles, Huberman, and Saldana (2014), with the following stages: Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing. Analysis shows that the implementation mechanism for transformational leadership (The Four I’s) is not uniform but rather tailored to the institution’s characteristics. At SMKN 3 Bone, the mechanism operates progressively and technically, with the principal translating the Intellectual Stimulation and Inspirational Motivation dimensions into concrete operational policies (research funding, industrial internships, and challenging work standards). This mechanism creates an innovation-oriented work culture. In contrast, at SMAN 11 Bone, the mechanism operates persuasively and administratively, with the principal predominantly using the Idealized Influence dimension through a personal approach and exemplary discipline to maintain stability. As a result, this mechanism appears to support teacher administrative compliance, but is not yet strong enough to drive a radical transformation in learning methods. This study provides context-specific qualitative evidence regarding differences in leadership implementation across two school settings, which can serve as a basis for more targeted leadership development and training policies for school principals.